تطبيق نماذج جداول الحياة على جماعات أسماك السردين Sardina pilchardus (Walbaum, 1792) - حسين, شيرين (Latakia University Journal -Biological Sciences Series, 2018)
This study is concerned with the life tables models, which depends mainly on the number of individuals within each age group and its applicability to marine populations. This model was applided on the Sardina pilchardus species as an example of marine fish stocks, in order to describe the nature of the biological changes that occur in such population, in terms of survival and mortality rates at various age groups and life expectancies. The results showed that: (i) Sardina pilchardus mortality rates were low during the first two years of life and then began to increase for the rest of age groups where their survival curves were declining; (ii) the net reproductive rate was higher than 1, so the sardine population size was increasing, (iii) the average lifespan of the generation was 3.8 years; (vi) the annual population growth rate of this species was high, and this population was able to doublicate itself over a period of time not exceeding 1.36 years. يهتم هذا البحث بدراسة نماذج جداول الحياة والتي تعتمد بشكل أساسي على أعداد الأفراد ضمن التركيبة العمرية للجماعة وإمكانية تطبيقها على الجماعات البحرية. تمّ تطبيق هذا النموذج على أحد أنواع أسماك السردين Sardina pilchardus كمثال على المخزونات البحرية، بهدف وصف طبيعة التغيرات الحيوية التي تطرأ على هذه الجماعة من حيث قابلية البقاء على قيد الحياة في المراحل العمرية المختلفة والنسب المئوية لنفوقها وكذلك توقع مدة الحياة. بينت نتائج البحث أنّ مُعدّلات نفوق هذه العينة من أسماك السردين Sardina pilchardus تبدأ منخفضة بالنسبة لأفراد السنتين الأولى من عمرها ومن ثمّ تبدأ بالازدياد بالنسبة لبقية الأعمار، وأنّ منحنيات البقاء لها تأخذ شكلاً هابطاً؛(ii) إنّ قيمة مُعدّل التكاثر الصافي أكبر من الواحد وبالتالي جماعة هذا النوع في حالة تزايد؛ (iii) بلغ متوسط طول مدة حياة الجيل 3.8 سنة؛ (vi) معدل النمو السنوي لهذا النوع مرتفع، وأنّ هذه الجماعة قادرة على مضاعفة نفسها خلال مدة زمنية لا تتجاوز 1.36 سنة.